2007
DOI: 10.1017/s1368980007246762
|View full text |Cite
|
Sign up to set email alerts
|

Diet and overweight and obesity in populations of African origin: Cameroon, Jamaica and the UK

Abstract: Objectives: To determine the relationship of diet to overweight and obesity among populations of African origin. Design and setting: Cross-sectional data were obtained from adults aged 25-74 years in rural Cameroon (n ¼ 686), urban Cameroon (n ¼ 975), Jamaica (n ¼ 924) and Afro-Caribbeans in the UK (n ¼ 257). Dietary data were collected using foodfrequency questionnaires specifically designed for each site. Body mass index (BMI) was used as a measure of overweight. Results: The expected gradient in the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
2
22
1
3
Order By: Relevance
“…Obesity is significantly more common in middle-aged women than in men, and ethnic minority women are remarkably affected as compared to their male counterparts in western countries. 16,17,[25][26][27][28][29] In this present study, for example, nearly 43% of AfricanSurinamese women were obese compared with 18% of African-Surinamese men whereas 27% of Hindustani women were obese compared to 15% of Hindustani men. Although the relationship between obesity and hypertension is firmly established, the underlying mechanisms are not well understood.…”
Section: Blood Pressure Levelssupporting
confidence: 44%
“…Obesity is significantly more common in middle-aged women than in men, and ethnic minority women are remarkably affected as compared to their male counterparts in western countries. 16,17,[25][26][27][28][29] In this present study, for example, nearly 43% of AfricanSurinamese women were obese compared with 18% of African-Surinamese men whereas 27% of Hindustani women were obese compared to 15% of Hindustani men. Although the relationship between obesity and hypertension is firmly established, the underlying mechanisms are not well understood.…”
Section: Blood Pressure Levelssupporting
confidence: 44%
“…In this study, 47.3% of women were overweight or obese. Although this rate is lower than the national prevalence (56.6%) (22), it is higher than in rural communities in Cameroon (9.5%) and Nigeria (4.2%) and similar to rates in urban female subjects in Cameroon (47.0%) (16,23). The proportion of those who were obese in this study (22.6%) also is lower than the national estimate (31.8%) or in semiurban (40.2%) and urban (43.9%) South African women but higher than in rural Nigerians (2.4%) and rural (0.7%) or urban (10.0%) Cameroonians (16,22,23).…”
Section: Discussionmentioning
confidence: 58%
“…Although environmental factors are important determinants of obesity (92,132), studies have also identified candidate loci that contribute to the onset of this disease. For example, the human uncoupling gene UCP3 has been correlated with obesity and lower resting energy expenditure in African Americans and the Mende tribe of Sierra Leone (10,100); in contrast, risk for obesity associated with this gene varied among non-African populations (48,134,152).…”
Section: Obesitymentioning
confidence: 99%